A practical approach to online-course development in Malaysia - M., Sapiyan; Mansor Fadzil; Kaur, Abtar (2007)
Many universities in Malaysia started their open learning programs early this decade. The University of Malaya began its own program in 1994. Since then many has debated the wisdom of the program. However, with the recent advancement made in the computer technology the University of Malaya, have accepted that open learning is here to stay. Thus, our effort now concentrates on how the program can be made to work effectively.